Rancang Bangun Sistem Informasi Pelayanan Pelanggan (Studi Kasus UD. REMAJA MOTOR) - Dewi, Ketut Rini A.; Wibowo, Januar; Amelia, Tan (Jurnal JSIKA, 2012)
UD. Remaja Motors is a business entity engaged in three areas, namely the sale of goods, sales of services and warehousing. The company is indirectly every day will provide service to its customers. But this time, customer service is still not up. The Company does not have adequate systems to manage customer data and also do not know the needs of its customers. Customer Service Information System by implementing Customer Relationship Management (CRM), which is useful to improve service to customers, both in terms of sales of goods services and sales services. Desktop applications provide the recording and processing of customer data and customer transaction data. The system also provides information that will be delivered to customers via SMS Gateway integrated with the desktop. While the web application provides the facility online catalog and ordering system stuff. After doing the design and manufacture of the system, it is expected that the system can provide a solution to overcome the problem of transaction services directly and more efficient, easier to obtain information, and the company can maintain good relations between companies producing services through continuous service to customers. Keywords: information systems, customer service